Synthesis of Artificial Magnetic Conductors Using Structure-Based Evolutionary Design - Luisa Deias; Giuseppe Mazzarella; Giorgio Montisci; Giovanni Andrea Casula (International Journal of Antennas and Propagation)
An evolutionary programming approach, the so-called structure based evolutionary design, is applied to the synthesis of planar periodic electronic band gap in order to obtain an artificial magnetic conductor surface. We show that this strategy, in conjunction with a flexible aperture-oriented approach, allows for obtaining new and effective structures. This almost unique ability is exploited to obtain an artificial magnetic conductor periodic surface with a bandwidth larger than the most popular surfaces known so far.